Identifying especial skills for air gun shooting in skilled male and female shooters - Kashani, V. O.; Nikravan, A.; Azari, M. (Annals of Applied Sport Science, 2016)
The present study attempted to investigate the emergence of especial skill in shooting with air gun at two skill levels (skilled, novice). The population studied here included all male and female shooters from the city of Semnan. The study was conducted on a sample of 40 shooters, consisting of two groups of women with the mean age of 21.33±2.26 and two groups of men with the mean age of 23.44±23.44, who displayed their shooting abilities with air guns from five points (8, 9, 10, 11, 12 meters) from the target. The test was conducted in 4 sets (with 15-minute rest intervals) each consisting of 5 blocks of 25 with 20 shots at each point (100 shots in all). The gap between each set was the resting time of 15 minutes. A significant difference was found between the actual and predictive scores in all groups (p<0.05): the differences found between actual and predictive scores were significant at P=0.012 for skilled male shooters, P=0.023 for novice male shooters, P=0.001 for skilled female shooters, and P=0.021 for novice female shooters. These findings of this study support the emergence of especial skill in all groups of air gun shooters.